Pyometra, an Unusual Case of Acute Abdomen - Kyle E. Nielsen; Sarah A. Medeck; Dan B. Brillhart; Kasey J. Mayclin (Clinical Practice and Cases in Emergency Medicine, 2018)
A 49-year-old female six days post-endometrial biopsy presented to the emergency department with constant severe suprapubic abdominal pain, fevers and myalgia. A contrasted computed tomography noted an intrauterine fluid collection and a final diagnosis of pyometra was made in the operating room following total hysterectomy. Pyometra is an exceptionally rare clinical condition with significant mortality.